Enhancement on UTP SAP Campus Management System - Abdul Kadar, Amir Ismail (Universiti Teknologi Petronas, 2006)
SAP Campus Management is a powerful solution for every constituent on campus life either to its executives, administration, faculty, or to its students. It also support the overall student life cycle from the registration process and up to the graduation. Some of student academic processes in UTP are not supported by SAP Campus Management solution. From here, the work to improve the system is initiated to help increase the productivity and to lessen the burden of the admin staffs in maintaining the student academic cycle in UTP. During the first part of the project, the two objectives have been completed which are to study and understand UTP Campus Management system's business processes and its framework and to identify for any potential area or business processes that can be improved and enhanced. Currently, for the second part of the project, the objective of the project is to design and develop the appropriate solutions or ABAP program in order to automate the audit graduation process. This project will only focus its area of study on improving existing UTP Campus Management system. Specifically, the project development will focus on graduation process only. The project has completed two phases from its four phases which is the planning phase and analysis phase. For this semester, design and implementation phases will be covered. Design phase is scheduled to end on end of February 2006 and implementation phase is scheduled to end on end of May 2006. By the end of the project, a complete report will be given to project supervisor and a complete program to support the required business process(s) will be produced.